Charles-Emmanuel Ier ou l’appel à être plus que soi-même - Stéphane Gal (Chrétiens et Sociétés, 2013)
Vocation was a determining element in the politics of legitimization deployed by the duke of Savoy Charles-Emmanuel I (1562-1580-1630). Convinced to have been chosen by the divine providence to realize an outstanding dynastic intention, he cultivated the wonderful to dilate his person, his States and his status in the size of a kingdom. Man of letters as much as man at arms, he expressed himself his expectations in poetries and drawings idealizing the Christian prince. His action as its works had to reveal him for what he was really: a prince called to reign as king.